Timber production value chain in three Belizean Mennonite communities - Vidal, Cristina (2012)
The study covered three Mennonite communities: Upper Barton Creek, Lower Barton Creek and Springfield, all of them located in Cayo District. With the lessons learned, suggestions for improving the production process will be given. It is also expected that the study will provide an incentive to other communities for timber production in agroforestry systems.